Developing a Mathematics Learning Application Using an Android-based Ethnomathematics Concept of Traditional Javanese Batik Pattern - Irawan, Ari; Lestari, Mei; Rahayu, Wanti; Dwitiyanti, Nurfidah (KnE Social Sciences, 2022)
Ethnomathematics is a part of the integration of mathematics and culture. This study aims to create an Android-based mathematics learning application using Javanese batik ethnomathematics material on flat shapes and their transformation properties. The method used in this research is Research and Development (R&D) with the ADDIE model (analysis, design, development, implementation, and evaluation). The authors examine traditional batik motifs of West Java, Central Java, and East Java to develop ethnomathematical learning media for an Android-based learning media application. Needs analysis and ethnomathematical analysis of batik motifs from each region were done. Next, the screen display for each page of the material was designed. The research is currently ongoing and is in the development stage. Keywords: ethnomathematics, Javanese batik, batik pattern, learning media, mathematics